The Against Nature Journal : Issue #1 : Summer 2020. - Arriola, Aimar; Castéra, Grégory; Ash, Dayna; Bouzid, Naoufal; Danladi, Chekwube; Daston, Lorraine; Dhall, Pawan; Divan, Vivek; Dore, Amatesiro; Jones, Eliel; Mugo, Kari; Nissinen, Martti; et al. (Paris : Council, 2020)
This inaugural issue – edited by Aimar Arriola – outlines the intersections between legislation, human rights activism, and spirituality. We celebrate the magical legacy of the late writer BINYAVANGA WAINAINA with his first piece of fiction, accompanied by an essay on his lifework by AMATESIRO DORE. The issue also includes legal scholar VIVEK DIVAN’s commentary on a seminal verdict in the history of “crime against nature” laws from India, essays on non-normative approaches to spirituality and religion by MARTTI NISSINEN and LINN MARIE TONSTAD, poetry by ABU NUWAS and CHEKWUBE DANLADI, an inspiring text on the moral authority of “nature” by science historian LORRAINE DASTON, images from the colonial period in Vietnam by artist DANH VO, and columns on recent events in Barbados, Brazil and Abya Yala, India, Kenya, Lebanon, Malaysia, Morocco, and Poland by DONNYA PIGGOT, VIVANE VERGUEIRO, PAWAN DHALL, KARI MUGO, DAYNA ASH, NIZA, NAOUFAL BOUZID, and ELIEL JONES.
artist contribution Danh Vo
T.A.N.J. is a biannual arts and human rights magazine exploring "crime against nature" laws and their legacies, in print, in person, and online.
boek